Measuring the dynamic stiffness of resilient materials using ESS and MLS signals. (September 2018) - Guidorzi, Paolo; Barbaresi, Luca; Garai, Massimo
Highlights: Dynamic stiffness of resilient materials is measured using ESS and MLS signals. It is explained that ESS and MLS are compatible with the ISO 9052-1 prescriptions. Hammer generated impulses, white noise, ESS and MLS are compared on different materials. The comparison shows that ESS and MLS signals are viable alternatives to traditional techniques. Abstract: Resilient materials are used to reduce vibration transmission in buildings, e.g. in floating floors designed to decrease the impact sound pressure level in the room below the floor. The performance of a floating floor can be estimated in advance knowing the dynamic stiffness per unit area of the resilient material, which is usually measured on a small sample according to ISO 9052-1. Thus, the reliability of results from ISO 9052-1 measurements is crucial. However, the published standard gives few indications on the measuring equipment and suggests measuring the resonance frequency of the fundamental vertical vibration of the test specimen and of the load plate by using either sinusoidal, white noise or pulse signals, considered as equivalent. In this work, a measuring apparatus following the ISO 9052-1 specifications with some hardware and software improvements is described. Then the scanty specifications about the excitation signal are complemented introducing two robust alternatives, compatible with the ISO 9052-1 prescriptions: the ESS (Exponential Swept Sine) and MLS (Maximum Length Sequence) signals. The two newly proposed signals are validated measuring the dynamic stiffness per unit area of different resilient materials, whose resonance frequency is estimated using the same measuring equipment and four different excitation methods: hammer generated impulses, white noise, ESS and MLS. The comparison shows that ESS and MLS signals, already in use since many years for other kinds of acoustic measurements, are viable alternatives to traditional techniques and may have advantages in term of repeatability, dynamic range, cleanness of the frequency response and background noise immunity.